The Pygmalion Effect in Education: A Review of Research Evolution and Future Directions - Li, Ruoyu (Journal of Educational Research and Policies, 2026)
The Pygmalion Effect has become a core topic in the fields of educational psychology and school leadership since Rosenthal and Jacobson’s pioneering research. This article aims to conduct a systematic integration and review of the research results based on core literature, clarifying the theoretical origin, mechanism of action, influencing dimensions, boundary conditions and educational intervention strategies of this effect. The review reveals that teacher expectations influence students’ academic achievements and psychological motivation through multiple mediating variables such as teacher-student interaction, students’ self-concept and self-efficacy. However, this effect is not unconditional and its strength and direction are significantly regulated by individual student factors (such as autonomy), classroom environment (such as ability grouping), teacher beliefs (such as growth mindset) and different analytical levels (such as individual and class). It may even trigger the “reverse Pygmalion Effect” or the “Golemb Effect”. Effective educational practices should combine high expectations with high support, and through teacher reflective training, classroom environment optimization and differentiated teaching to transform the expectancy effect into a positive educational force. This paper finally summarizes the limitations of existing research and indicates the direction for future research.